2021
DOI: 10.1038/s41586-021-03784-w
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic cooling of a trapped proton mediated by an LC circuit

Abstract: Efficient cooling of trapped charged particles is essential to many fundamental physics experiments1,2, to high-precision metrology3,4 and to quantum technology5,6. Until now, sympathetic cooling has required close-range Coulomb interactions7,8, but there has been a sustained desire to bring laser-cooling techniques to particles in macroscopically separated traps5,9,10, extending quantum control techniques to previously inaccessible particles such as highly charged ions, molecular ions and antimatter. Here we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…In this section, we have shown that our simulations are able to unambiguously reproduce the observed experimental signatures [12]. By giving access to the time domain data, the results provide another layer of understanding.…”
Section: Comparison Of Simulation Results To Experiments and Theorymentioning
confidence: 63%
See 4 more Smart Citations
“…In this section, we have shown that our simulations are able to unambiguously reproduce the observed experimental signatures [12]. By giving access to the time domain data, the results provide another layer of understanding.…”
Section: Comparison Of Simulation Results To Experiments and Theorymentioning
confidence: 63%
“…Reference [12] employed the coupling scheme with a common RLC resonator. First, the coupling between the proton and 9 Be + ions was demonstrated above the resonator temperature by bringing the proton to resonance with excited beryllium ions.…”
Section: Comparison Of Simulation Results To Experiments and Theorymentioning
confidence: 99%
See 3 more Smart Citations